Partial protection against tissue cysts formation in pigs vaccinated with crude rhoptry proteins of Toxoplasma gondii - Garcia, J. L.; Gennari, S. M.; Navarro, I. T.; Machado, R. Z.; Sinhorini, I. L.; Freire, R. L.; Marana, ERM; Tsutsui, V; Contente, APA; Begale, L. P. (Elsevier B.V., 2005)
A vaccine containing crude Toxoplasma gondii rhoptry proteins incorporated in the immunostimulating complexes (ISCOM) adjuvant was tested in pigs for protecting against tissue cyst formation. For this, 38 mixed breed pigs were divided into four groups, G1 (vaccinated challenged, n = 10) received two doses (100 mu g/dose) of the rhoptry vaccine at days 0 and 21, G2 (vaccinated challenged, n = 10) received viable tachyzoites (7 x 10(7)) of the RH strain at day 0, G3 (unvaccinated challenged, n = 10) and G4 (unvaccinated unchallenged, n = 8). Pigs were challenged with 4 x 10(4) VEG strain oocysts 57 days later. The G1 pigs produced high IgG antibody levels in the indirect enzyme-linked immunosorbent assay (ELISA) after the second dose of rhoptry vaccine, but were not clinically protected against a high dose oocyst challenge. Partial protection was observed in G1 at the chronic phase of infection, when compared with G3. Pigs in group 2 developed high antibody levels and were protected against clinic signs. T gondii was not detected in two (G1) and three (G2) pigs by mouse bioassay. The results indicate partial protection in pigs vaccinated with a rhoptry vaccine. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; rhoptry proteins; pigs; vaccination; protection